An Analysis of Interpersonal Meaning in Senior High School Students' Discussion Essays - Marisa Dwi Puspitasari (International Journal of English Education and Linguistics (IJoEEL), 2026)
Interpersonal meaning plays a crucial role in academic writing, particularly in discussion essays that encourage students to present arguments and engage readers. However, research on these texts remains limited. This study aims to analyze interpersonal meaning in eleventh-grade students’ discussion essays through the system of mood and modality in Systemic Functional Linguistics. This study employs a qualitative descriptive method by analyzing 14 essays at the clause level. The results indicate that the declarative mood is the most dominant, with 404 positive clauses and 30 negative ones., while the interrogative and imperative moods are used sparingly. Regarding modality, modalization was more dominant than modulation. This indicates that students tend to express their opinions cautiously. Overall, students’ understanding is quite good, but their application still needs improvement.